There is a bird on your head! - Willems, Mo. (New York : Hyperion Books for Children, an imprint of Disney Book Group, 2007)
Opposite best friends Gerald, who is careful and worrisome, and Piggie, who is clumsy and carefree, run into a problem when two birds land on Gerald's head.
Horn Book Starred
Notable/Best Books (A.L.A.)
School Library Journal starred
Horn Book Starred, April 2008
Horn Book, January 2008
Notable/Best Books (A.L.A.), January 2008
Keywords: Animals -- Juvenile fiction; Birds -- Juvenile fiction; Animals -- Fiction; Birds -- Fiction; Animals -- Fiction; Birds -- Fiction; Humorous fiction; Readers (Publications)